Brejos dos Crioulos no sertão norte mineiro: desordem e rearranjos em territórios relacionais - Salgado, Hebert Canela (2015)
PhD study, inserted in the territorial geographic reading studies highlights the social spatial context of new political subjects seeking to requalify their life space through diverse confronts, in the appropriation of recognition spaces. Occupying positions of power, and in many relationships, territorial processes consolidate the social, material and symbolic reproduction of the community. Consequent the territory recognition, titration and legitimacy manifested as a challenge. The thesis presents the Brejo dos Crioulos as a relational territory from field research, documental and bibliographic research, in the participation, perceptions and observation of relations, approaches, distances and acclimated experiences, in the last four years of the territory and, its relation processes, in the context of land conflicts, validation of constitutional rights and in the exercise of citizenship through the struggle for the right to maintain their daily routine, their ways of life, production modes, relations, identity and culture, focused on life that keeps the place-territory‟ called by them Brejo dos Crioulos. This research is intended to analyze how the heterogeneity from quilombolas‟ territory can be read in the geographic space, considering the specialties between propriety, appropriation, territory and territorialities, in the context of spatial homogenization by globalization. The geographic aspects indicates an immersion in the comprehension of the regional territorial processes, resulting historically from the diaspora of the black people from the north of Minas to a reflection about the production of the Brejo dos Crioulosquilomba traditional territory in the space of struggle, from relations established in many power fields, specialized in the in the context of the quilombola issue in Brazil. The symbolic power materialized regarding the historic oppression of the land property and the flexibility of the Brazilian state of territorial rights from traditional people and communities in part of the SertãoGerais creates new opportunities for reflection about collective rights and constitutional assurances. In this context it is understood that the spatial production from what is presented as place-territory‟ Brejo dos Crioulos is a result of the relational propriety of the territory in the multi dimensionalities from the space lived and the used territory. The cultural landscape of its spatial identity, its existential content, producers and power managers feeds the spatial developments and the expansion of new frontiers. From the fusion of the brejeiro and crioulo space, the relational territory is then designed as a synthesis of social content and the spatial forms that translates its existence. In this case, comprehend the frontier relations between commoditized spaces for the disorders and not commoditized territories that from its spatial relations produces the development of its existence by the critic geographic action resulting in the relational territory.